Decision Options - Eapen, Gill (Chapman & Hall/CRC finance series., 2009)
Although uncertainty and flexibility are important attributes that drive the value of an investment, they are seldom systematically considered in traditional financial analysis. Through theory and case studies, Decision Options: The Art and Science of Making Decisions details how uncertainty and flexibility can be evaluated to assist in making bett.